(untitled) (Revista Brasileira Multidisciplinar, 2025)
Sustainability aims to balance current needs with the future capacity of our planet, ensuring that present generations do not compromise future generation. Achieving sustainability in the energy context involves adopting practices to minimize waste and reduce the environmental impact associated with energy generation and consumption. Sustainable measures include implementing renewable energy sources such as solar and wind, and promoting conscious consumption behaviors. In this regard, this study assessed the impact of reducing electricity consumption in households of students enrolled in the Integrated High School at the State Technical School José Martimiano da Silva, after implementing sustainable practices learned in the Physics class. To evaluate the reduction in electricity consumption, students measured consumption in kWh by reading residential electricity meters. A reduction in electricity consumption was found in 88% of the analyzed sample, ranging from 191 kWh to 88 kWh, following the implementation of sustainable measures focused on reducing consumption. Additionally, participants from each course presented various ideas for mitigating energy consumption, spanning from the application of smart technologies and systems to the implementation of efficient design strategies, data analysis, and administrative management. Thus, the results underscore the importance of educational programs in raising awareness and promoting changes in energy consumption behavior.